Trifluoromethane modification of thermally activated delayed fluorescence molecules for high-efficiency blue organic light-emitting diodes. Issue 59 (10th July 2018) - Yokoyama, Masayuki; Inada, Ko; Tsuchiya, Youichi; Nakanotani, Hajime; Adachi, Chihaya
Abstract : Highly efficient blue and green thermally activated delayed fluorescence (TADF) molecules bearing trifluoromethane-modified carbazole groups were developed. Abstract : Highly efficient blue and green thermally activated delayed fluorescence (TADF) molecules bearing trifluoromethane-modified carbazole groups were developed. The trifluoromethane groups on carbazole induced blue-shifted emission and improved the photoluminescence quantum yield. The photostability of the TADF molecules was strongly related to the modification position of trifluoromethane on carbazole.